Hak Mewaris Anak Luar Kawin Berdasarkan Pengangkatan oleh Kakeknya Menurut Hukum Waris Adat Bali - Putra, I Gusti Ngurah Bayu Pratama; Budiono, Abdul Rachmad; Susilo, Hariyanto (Universitas Negeri Malang, 2020)
This study discussed the Balinese customary law regarding the position and inheritance rights of natural children who were adopted by their grander. This study used an empirical legal study, which was a method of legal study that sought to see and examine the law can work in people’s lives. The results of the study showed that the adoption of a natural child by his grandfather was legal according to Balinese customary law, the position of a natural child adopted by his grandfather was the same as his biological child. State law only had a role to strengthen the prevailing customary law. The right to inherit natural children who were adopted by their grandfathers were the same as biological children, including the inheritance of their rights and obligations both as a child and as a member of an indigenous village community.